Clinical and in vitro phenotype profiles of artemisinin-resistant Plasmodium falciparum K13 mutant alleles at the Thailand-Myanmar border - Nosten, F; Boullé, M; Witkowski, B; Duru, V; Sripawat, K; Nair, S; McDew-White, M; Anderson, T; Phyo, A; Menard, D (Centre for Disease Control, 2016)
Plasmodium falciparum artemisinin resistance (ART-R) may have evolved independently in various areas of the Greater Mekong Sub-region (1, 2), prompting the World Health Organization to change its regional policy from containment to elimination (3). Risks associated with ART-R include compromised use of artemisinin combined therapy (ACT), partner drug resistance selection, total ART-R resistance and geographical extension to other malaria endemic regions (2, 3). We therefore need to characterize ART-R in each independent setting and rapidly update the list of ART-R makers.